'Smart' wound dressings for advanced wound care: a review. (2nd July 2020) - O'Callaghan, Suzanne; Galvin, Paul; O'Mahony, Conor; Moore, Zena; Derwin, Rosemarie
Abstract : Hard-to-heal wounds are a common side-effect of diabetes, obesity, pressure ulcers and age-related vascular diseases, the incidences of which are growing worldwide. The increasing financial burden of hard-to-heal wounds on global health services has provoked technological research into improving wound diagnostics and therapeutics via 'smart' dressings, within which elements such as microelectronic sensors, microprocessors and wireless communication radios are embedded. This review highlights the progress being made by research groups worldwide in producing 'smart' wound device prototypes. Significant advances have been made, for example, flexible substrates have replaced rigid circuit boards, sensors have been printed on commercial wound dressing materials and wireless communication has been demonstrated. Challenges remain, however, in the areas of power supply, disposability, low-profile components, multiparametric sensing and seamless device integration in commercial wound dressings.